Integrated Industry Relevant Research Initiatives to Support Geometallurgical Mapping and Modelling - S Walters (The Australasian Institute of Mining and Metallurgy, 2011)
The emerging discipline of ‘geometallurgy’ is not new but is becoming increasingly recognised as a discrete and high-value activity. Geometallurgy involves a quantified and spatially constrained approach to ore characterisation in terms of relationships to critical processing performance behaviours. A key outcome is enhanced economic optimisation of mining and improved risk management tools.Industry recognition of the need for large-scale, integrated research to support this emerging area resulted in commencement of a major ongoing initiative in mid-2005. The AMIRA International P843 ‘GeMIII’ project (Geometallurgical Mapping and Mine Modelling) is a cross-discipline collaboration involving a number of world-class research organisations supported by over 20 industry sponsors.The project is delivering integrated tools and methods which link intrinsic rock characteristics to prediction of mineral processing performance. These indices must be capable of spatial distribution in 3D resource models and incorporation into mine planning and optimisation. A key aspect is provision of new cost-effective tools and methods which can provide the large numbers of measured and estimated data points required to undertake effective modelling and spatial distribution. The integrated methodology and enabling technologies being developed through the ongoing AMIRA GeMIII project are outlined, together with implications for supporting industry best practice.